ҚОРАҚАЛПОҒИСТОН ЎЗБЕК ШЕВАЛАРИДАГИ ТАОМ НОМЛАРИНИНГ СИНТАКТИК УСУЛ БИЛАН ЯСАЛИШИ - Худаярова, М.Т. (SCIENCE and SOCIETY, 2020)
The article examines the syntactic preparation of food names in the Uzbek dialects of Karakalpakstan. In the Uzbek dialects of Karakalpakstan, there are many examples of the formation of food names in a syntactic way rather than morphological methods, the number of words in food names, the methods of connection, the relationship between the components, and so on.
Keywords: food names; Uzbek dialects; word formation; syntactic method; free compounds; stable compounds; simple product names; complex product names; connection methods; pleonasm